A influência da frequência respiratória sobre os gases sanguíneos arteriais no pós-operatório imediato de laparotomia exploradora por trauma abdominal - Matos, Carlos José Oliveira de (2006)
The incidence of post-operative pulmonary complications is large, in consequence of the manipulation of abdominal cavity with changes on pulmonary volumes and capacities, resulting in atelectasis and hypoxemy. Alteration of breath pattern in association with postoperative pain can interfere in gaseous exchanges with larger repercussions in the presence of risk factors. Respiratory rate and arterial blood gases have an important role on the assessment of lung function, specifically on pulmonary ventilation and gaseous exchanges, monitoring carbonic gas arterial pressure and oxygen arterial pressure. The objectives of this research were: analyze the influence of respiratory rate on arterial blood gases at immediate postoperative of exploratory laparotomy for trauma, observe arterial gases concentrations, respiratory rate and oxygenation index in the first three post-operative days. Moreover, analyze if there is a correlation between respiratory rate on arterial gases, and carbonic gas arterial pressure on oxygen arterial pressure in the first three post-operative days. It was a non-experimental cohort study of analytic and descriptive character from April to September 2005 at Governador João Alves Filho Hospital, in Aracaju, during the first three postoperative days. 55 patients of both gender with ages between 18 to 62 were assessed, submitted to exploratory laparotomy for trauma in urgent character. As criteria for inclusion, there were urgency surgical procedures, with xipho-pubic incision, general anesthesia with time larger or equal to 120 minutes, where the respiratory rate and arterial blood collected were measured according to American Association for Respiratory Care guidelines to assess arterial blood gases partial pressures. After collecting the blood the PaCO2 and PaO2 values were achieved and calculated the oxygenation index through PaO2/FiO2 formula. The data were analyzed by SPSS 10.0 software through median, and standard deviation, ANOVA test to analyze the variation between the average median, Tukey test to analyze the difference between significant median and simple linear correlation to observe the behavior of tendencies among the variables, all in significance level of 95% or p<0,05. the study was approved by Ethics Committees of Human Search of Federal University of Sergipe. The outcomes showed median for respiratory rate from 27,49 ±5,31 bpm (24 h), 25,35 ± 5,32 bpm (48 h), 24,15 ± 3,94 bpm (72 h). For PaCO2 median of 32,84 ± 4,49 mmHg (24 h), 33,65 ± 3,36 mmHg (48 h), 34,04 ± 3,73 mmHg (72 h). For PaO2 median of 85,29 ± 18,30 mmHg (24 h), 87,53 ± 17,56 mmHg (48 h), 89,31 ± 16,57 mmHg (72 h). The analysis of median in the first three post-operative days by ANOVA presented statistic significance only for respiratory rate (p<0,05), while for PaCO2 and PaO2 presented p>0,05. Comparing the variables, it was observed correlation between RR x PaCO2 regular in 24 h (r= - 0,42604), weak in 48 and 72 h (r= - 0,23857 and -0,02807), between RR x PaO2 weak correlations at 24, 48 and 72 h (r= 0,02339, 0,02305 and -0,0505). This was, our survey concludes that RR presented a significant variance at the three post-operative days and a significant correlation of RR and PaCO2